Estimation of internal ballistic parameters for the 107 mm rocket motor conceptual design (Defense and Security Studies, 2024)
The demand for solid propellant rocket motors does not seem to fade, regardless of constant improvements in rocket technology. To make modifications that will result in improved design, it is crucial to use already existing motor models. Setting internal ballistic requirements and conducting calculations by following the design sequence, results in defining pressure- and thrust-time curves that are needed for rocket motor performance evaluation and providing a base for further external ballistic analysis. Calculation results are obtained by using the program SPPMEF, which is divided into modules for different parts of internal ballistic analysis using equations and shortens the time needed for theoretical integrations. NGR-176 is a type of double-base solid rocket propellant selected for the conceptual design of 107 mm rocket motor. The selected propellant configuration is a star with adapted and optimized geometric variables and new structural materials have been assigned to the newly-sized nozzle and motor case through examining various parameters.